Análise do perfil legal do ofício do tradutor jurídico no Brasil - Fröhlich, Luciane (Language and Law / Linguagem e Direito, 2017)
Legal translators work in different kinds of situations, with written translations (sworn or not) of such forensic texts as powers of attorney, not sure what this is legal Codes, statutes, letters of request, wills, etc.) and as interpreters in Police Stations, Solicitors offices, Courts etc.), and at times as valuators, investigating the translations of third parties. This provision of ultra-specialized services generates obligations on the translator, who must strive for excellence. Furthermore, legal translation is concerned with legal texts with highly complex terminology, whose validation involves various challenges for the legal translator must deal. Moreover, it should be noted that legal translation creates both civil and criminal liability for the translator, which is why the translator needs to know not only the laws and regulations referred to the texts to be translated, but also those governing their profession. This paper presents an annotated analysis of such regulations, compiled in order to trace the legal profile of legal translation in Brazil, with special attention to the state of Santa Catarina.